Rhetorical Strategies Used in Indonesian Persuasive Essays Written by Students Majoring in Indonesian and in English - Bambang Budi Cahyono (Universitas Negeri Malang, 2016)
This study was aimed at comparing rhetorical strategies used in the Indonesian persuasive essays written by students majoring in Indonesian and those majoring in English. Two groups were involved: the third-year students of the Department of Indonesian Language and Literature and the fourth-year students of the English Department of the State University of Malang. They were asked to write persuasive essays on whether violence on TV programs should be restricted. The results showed that there was a significant difference between the rhetorical strategies in Indonesian persuasive essays written by students majoring in Indonesian and those written by students majoring in English. In general, the essays written by the students majoring in English were more successful than those written by the students majoring in Indonesian in terms of the superstructure of argument, the Toulmin model of informal reasoning, and the persuasive appeals